Information-seeking behavior and information needs of diocesan seminarians, religious and lay students of St. Vincent School of Theology - Urcia, Maylene U.; Faderon, Rosalie B.; Dela Torre, Nathalie N. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2009)
Information seeking is important to satisfy one's information needs. Information needs vary and may result to different information-seeking behavior. Information can be found in multiple sources. There are several factors that affect the choice of information source such as reliability, relevance, scope and novelty of the information contents. Availability and access also affect the choice of an information source. Online information seeking is popular among different disciplines in the society.
The study's main objective was to determine the information needs and information-seeking behavior of diocesan seminarians, religious, and lay students of St. Vincent School of Theology. The descriptive method of research was used in acquiring the information needed. In particular, survey questionnaires were administered to the students with different affiliations, courses, and year levels of St. Vincent School of Theology.
The principal findings show that majority of the respondents (41.67 or 50) fall within the age group of 26-30 years old. The findings also show that majority of the students are male because they are seminarians from different seminaries and congregations. Most of the students, especially seminarians, in St. Vincent School of Theology, graduated with the degree of A.B. Philosophy. Young professionals who entered the seminary attained their bachelor's degree in engineering, psychology, education, nursing, chemistry, etc. from different universities and colleges outside the seminary. Moreover, there are more students in the first year level and the number decreases as they reach the fourth year level. Majority of the respondents visit the library not only because they want to use the library resources but also because the library is a place conducive for study and concentration. Theological information is the number one type of information they needed. This was followed by specific theological theories as indicated by 16.67 or 20 diocesans, 46.67 or 56 religious, and 2.5 or 3 lay students. In addition, application of theories was the most important type of information for 14.17 or 17 diocesans, 42.5 or 51 religious, and 4.17 or 5 lay students. Consulting a librarian was the method employed by most of the diocesans (16.67 or 20), religious seminarians (46.67 or 56), and lay students (4.17 or 5). Encyclopedias were considered as those that contain the most useful information as indicated by 19 diocesans (15.83), 63 religious (52.5), and 4 lay students (3.33) for their information needs. Most of the respondents used the internet; 95.83 or 115 answered "yes : and only 4.17 or 5 of them answered "No".
Vita.
Special Problem (Master of Library and Information Science)
Keywords: Seminarians -- Philippines -- Quezon City; Theological seminary libraries -- Philippines -- Quezon City -- Use studies